Optimasi Sistem Usahatani Terintegrasi untuk Memaksimalkan Pendapatan Petani - BUDIASA, I WAYAN; AMBARAWATI, IGAA; MEGA, I MADE; BUDIASA, I KETUT MANGKU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2012)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT Optimizing Integrated Farming System to Maximize Farmers’ Income This study aims to find out the optimal model of integrated farming system (SIMANTRI) development in farmers’ group of SIMANTRI 074, Jemberana Regency. Primary data by using survey method collected from 20 farmers of the group and secondary data gathered from any sources were used to specify parameters of the model. Linear programming analysis by using software BLPX88 is to solve constrained optimization problem in the model. A small farmer, which his farm size is 0.48 hectare, was optimal in allocating resources to conduct many farm activities under the SIMANTRI indicated byfrom optimal solution of the model which conforms to observed behavior. The maximum farmers’ income, generated from the optimizing process was Rp26,041,250 per annum. Key words : optimization, integrated farming system, income